PENGARUH GROWTH OPPORTUNITY, PROFITABILITAS DAN STRUKTUR ASET TERHADAP STRUKTUR MODAL - Selfiana, Kiki Eka; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of growth opportunity, profitability, and assets structure to the capital structure, the research population is automotive companies which are listed in Indonesia Stock Exchange in 2011-2014 periods. The research sample has been selected by using purposive sampling technique; 9 companies (36 firm years) which meet the criteria have been obtained as samples. The data analysis technique has been done by using multiple regressions and hypothesis has been doneby using SPSS program 21 version. Based on the result of multiple regressions with its significance level is 5%, so the result of the research shows that: (1) Growth opportunity has an influence to the capital structure andits regressions valueshows positive correlation;(2) Profitability does not have any influence to the capital structure and shows a negative correlation, so the second hypothesis is denied. (3) the assets structural has an influence to the capital structure, anditsregressions value shows a positive correlation, so that the third hypothesis is accepted.Keywords: Growth Opportunity, Profitability, Assets Structure, Capital Structure.